Fairness Analysis Of Long-Term Debt Balance On Financial Statements Of Foundation A By KAP DS - Irma Novita Sari; Sri Trisnaningsih (International Journal of Economics, Management and Accounting, 2024)
The accuracy of debt balances is crucial because it can affect the credibility and financial health of the company. Therefore, an audit of debt is very necessary because if there is a misstatement of this item, it will affect the fairness of the presentation of the financial statements as a whole. This study aims to analyze the fairness of the long-term debt account balance in the financial statements of foundation A as of December 31, 2022. This research is a qualitative study that uses a descriptive analysis approach method where the author collects, compiles, and analyzes data obtained from Foundation A. The results showed that the debt balance of Foundation A was presented fairly in the financial statements. This conclusion is supported by evidence obtained through audit procedures performed, including examination of long-term debt details, confirmation of debt balances to creditors, and analysis of the presentation and disclosure of long-term debt in the financial statements. This study can be useful in providing insight into the importance of proper presentation and disclosure of long-term debt and help improve the quality and transparency of financial reporting.